Enhancing teager energy operator based on a novel and appealing concept: Signal mass - Guido, Rodrigo Capobianco [UNESP] (Elsevier, 2019)
In analogy with a spring-mass system, the original Teager Energy Operator (T) approximately models the energy of a discrete-time signal (x[·]) as the squared product of its amplitude (A) by its instantaneous frequency (Ω). Interestingly, this article shows that not only the mechanical entity but also x[·] has a mass (η) expressing the resistance in changing the signal amplitude over time. In addition, T is modified based on η so that A 2 ·Ω 2 is computed exactly in terms of x[·], creating an enhanced energy operator (T) which allows for more precise analyses in contrast to those provided by the original tool. Lastly, illustrative examples are included to reassure the applicability of the proposed approach.